Biodegradable polymers—an overview1. (May 2014) - Doppalapudi, Sindhu; Jain, Anjali; Khan, Wahid; Domb, Abraham J.; Katzhendler, Joshua; Domb, Abraham J.
<x xml:space="preserve">Abstract</x> The revelation of biodegradable polymers dates back to many years ago. From then, their emergence leads to the surge of many biomaterials applicable in various fields like controlled drug delivery, regenerative medicine, orthopedic and long‐term implants which proved out to be momentous contributions of these materials. The immense effort and investigation kept on these materials are reflected by significant upsurge of the biodegradable polymer‐based marketed products and ongoing clinical trials of these materials. The synthetic versatility and flexible features of these polymers to get custom designed in accordance with need make them attractive for various therapeutic strategies. Long‐term biocompatibility and avoidance of surgery to remove implants are the main advantages of biodegradable materials over biostable polymers by which the former stand in for various indications over the latter. This review gives an overview on various biodegradable polymers with details on properties, mode of degradation and the potential biomedical applications associated with them. Copyright © 2014 John Wiley & Sons, Ltd.